The Precautionary Principle, Evidence-Based Medicine, and Decision Theory in Public Health Evaluation - Fischer, Alastair J.; Ghelardi, Gemma (Frontiers in Public Health, 2016)
The precautionary principle (PP) has been used in the evaluation of the effectiveness and/or cost-effectiveness of interventions designed to prevent future harms in a range of activities, particularly in the area of the environment. Here, we provide details of circumstances under which the PP can be applied to the topic of harm reduction in Public Health. The definition of PP that we use says that the PP reverses the onus of proof of effectiveness between an intervention and its comparator when the intervention has been designed to reduce harm. We first describe the two frameworks used for health-care evaluation: evidence-based medicine (EBM) and decision theory (DT). EBM is usually used in treatment effectiveness evaluation, while either EBM or DT may be used in evaluating the effectiveness of the prevention of illness. For cost-effectiveness, DT is always used. The expectation in Public Health is that interventions employed to reduce harm will not actually increase harm, where “harm” in this context does not include opportunity cost. That implies that an intervention’s effectiveness can often be assumed. Attention should therefore focus on its cost-effectiveness. This view is consistent with the conclusions of DT. It is also very close to the PP notion of reversing the onus of proof, but is not consistent with EBM as normally practiced, where the onus is on showing a new practice to be superior to usual practice with a sufficiently high degree of certainty. Under our definitions, we show that where DT and the PP differ in their evaluation is in cost-effectiveness, but only for decisions that involve potential catastrophic circumstances, where the nation-state will act as if it is risk-averse. In those cases, it is likely that the state will pay more, and possibly much more, than DT would allow, in an attempt to mitigate impending disaster. That is, the rules that until now have governed all cost-effectiveness analyses are shown not to apply to catastrophic situations, where the PP applies.